Governance of Digital Transformation Initiatives: A Case Study of Industrial Engineering Program at Universitas Bakrie - Femil Ishak; Hoga Saragih (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explore the governance of digital transformation initiatives in the Industrial Engineering Study Program, Faculty of Economics and Social Sciences, Bakrie University. Using a descriptive qualitative approach, this study identifies and analyzes how the institution manages digital change, the challenges faced, and the impact on various aspects of education. Data was collected through in-depth interviews with leaders, lecturers, administrative staff, and students, as well as observation and study of relevant documents. The findings show that the success of digital transformation depends on strong leadership, integration of technology in the curriculum, data security policies, and an organizational culture that supports innovation. Active stakeholder engagement and effective risk management strategies also play an important role in overcoming digital challenges